PENGEMBANGAN USAHA KERAJINAN BULO BATTI DI DESA ALLAERE - Lebang, Paulus; -, Chahyono (Jurnal Ilmiah Ecosystem, 2016)
Allaere village Tanralili district's districts have Bulo plantation crops Batti 'the bamboo is unique and has not been used optimally. On its uniqueness bamboo craftsmen "Wal Ikran", as the partners have mamanfaatkan IbM 1 bamboo into various types of products such as bamboo crafts; and table and chairs, bench (bed), ceiling, and various souvenirs. Bamboo handicraft business partners who do IbM 1 has not been optimal in terms of quantity and quality. Skills and kretivitas in producing bamboo crafts artisans earned owned for generations. While on the other hand the number of sales bamboo gapoktan Allaere as IbM 2 are limited partners. The limited number and types of craft very well affect revenue bamboo craftsmen as partners IbM 1, Gapoktan Allaere as partners IbM 2.Objectives and targets that increase production and income and gapoktan Allaere bamboo craftsmen, doing crafts Bulo product diversification Batti ', farmers' groups could cultivate the plantation bamboo (bamboo), and conduct business management training.To achieve these goals and targets, methods of implementation through mentoring / training craft production and business management Bulo Batti '.The results achieved after the mentoring and training of production quantity and quality of bamboo handicraft production partners increased IbM 1 and 2 Gapoktan Allaere IbM partners have started treating himself the plantation. And finally after mentoring / business management training both the partners and the community has been able to plan / calculate business.